2008
DOI: 10.1038/cr.2008.279
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine neuron degeneration induced by MPP+ is independent of CED-4 pathway in Caenorhabditis elegans

Abstract: Dear Editor,Parkinson's disease (PD) is a common neurodegenerative disease characterized by progressive loss of dopamine neurons in the substantia nigra, and manifests the cardinal clinical symptoms of resting tremors, rigidity, bradykinesia, hyperkinesias and abnormal posture. In the 1980s a synthetic heroin contaminant, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), was discovered as a cause of parkinsonism in a group of drug addicts. Since then, mechanisms involved in 1-methyl-4-phenylpyridinium (MPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…To investigate the neuroprotective efficacy of P7C3A20, P7C3, and Dimebon from MPP + toxicity in C. elegans, we monitored dopaminergic cell death in a transgenic strain of worms in which dopaminergic neurons fluoresce green by virtue of GFP expression driven by the dopaminergic neuron-specific promoter dat-1 (15). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the neuroprotective efficacy of P7C3A20, P7C3, and Dimebon from MPP + toxicity in C. elegans, we monitored dopaminergic cell death in a transgenic strain of worms in which dopaminergic neurons fluoresce green by virtue of GFP expression driven by the dopaminergic neuron-specific promoter dat-1 (15). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The eight dopaminergic neurons of C. elegans have been fluorescently tagged with GFP using the DAT-1 promoter in neuronal transgenic strains BZ555 ([dat-1p::GFP]), BY200 [dat-1p::GFP, pRF4(rol-6(su1006)], and TG2435 ([dat-1p::GFP + rol-6(su1006)]) (Nass et al, 2002; Pu and Le, 2008; Masoudi et al, 2014; Cooper et al, 2015). Studying these cells in a genetic background of overexpressed α-synuclein or after treatment with the environmental toxin 6-OHDA has revealed that DA neurons degenerate with age and identified alleles that confer 6-OHDA resistance (Nass et al, 2005; Hamamichi et al, 2008).…”
Section: Caenorhabditis Elegans Models Of Parkinson's Diseasementioning
confidence: 99%
“…In addition to transgenic C. elegans models involving the overexpression or mutation of PD-linked genes to study the genetic causes of PD, environmental agents have also been used to study PD-related neuronal degeneration and cell death (Nass et al, 2002; Pu and Le, 2008; Ali and Rajini, 2012; Zhou et al, 2013). Previous studies have modeled the motor aspects of PD using in vivo exposure to toxins that cause an overload of ROS and disrupt the electron transport chain in mitochondria leading to neuronal abnormalities and eventually cell death (Varcin et al, 2012; Dias et al, 2013; Hwang, 2013; Chege and Mccoll, 2014).…”
Section: Caenorhabditis Elegans Models Of Parkinson's Diseasementioning
confidence: 99%
“…As shown in Figure 4, unexpectedly, 6-OHDA exposure did not influence the transcript levels of ced-4 , ced-3 , ced-9, and egl-1 in BZ555 nematodes, suggesting that these gene expressions may be not involved in 6-OHDA-mediated neuronal apoptosis in C. elegans . Interestingly, another neurotoxin 1-methyl-4-phenylpyridnium ion (MPP + ) that can trigger parkinsonism also destroys C. elegans dopaminergic neurons independent of ced-4 pathway [38]. However, a recent study has shown that 6-OHDA activates the mitochondrial apoptosis pathway including the release of cytochrome c to cytosol and the activation of caspase-3 in rat adrenal phaeochromocytoma PC12 cells [39], indicating that other mechanisms may contribute to 6-OHDA-induced neuronal apoptosis.…”
Section: Resultsmentioning
confidence: 99%